Management of Side-Effects of Selective-Serotonin Re-Uptake Inhibitors in Children and Adolescents - Patel, Dilip R.; Udenberg, Katie J.; Choi, Patricia; Soares, Neelkamal (Current Psychopharmacology, 2018)
Background: Selective serotonin reuptake inhibitors are the recommended and most commonly used antidepressant medications for children and adolescents. This class of medications has been considered generally safe with few significant treatment emergent adverse reactions that generally abate over time. All antidepressants carry the precautionary warning for potential increase in suicidal ideation and close monitoring is recommended. Management of side effects of this widely used class of drugs is an important aspect of any medical practice that cares for children and adolescents. Objective: To provide a succinct and clinically relevant review of side effects of SSRIs and their management in clinical practice. Method: A literature search was done of relevant published articles in English language in the Medline database. Results and Conclusion: Gastrointestinal side effects are most common with the use of SSRIs and generally are tolerable and do not need discontinuation of the medication. Cardiovascular side effects are uncommon; however, prolonged QT syndrome has been reported. In utero exposure results in a constellation of signs and symptoms in the newborn called poor neonatal adaptation syndrome. In utero exposure also is associated with teratogenicity. Although less frequent, symptoms suggesting behavioral activation, switching, serotonin syndrome and discontinuation or withdrawal syndrome need careful evaluation and management.
Keywords: behavioral activation